Changes in eccentric utilization ratio, reactive strength index and leg stiffness in highly trained sprinters between training phases - Wlodarczyka, M. P.; Kusya, K.; Zielinskiaa, J. (Acta Kinesiologica, 2024)
Purpose: To determine changes in eccentric utilization ratio (EUR), reactive strength index (RSI), squat jump (SJ) and countermovement jump (CMJ) parameters in elite sprinters from the preparation phase to the competition (indoor) phase.